Development of Interactive Arabic Language Learning Modules Using Articulate Storyline 360 for 10th Grade Madrasah Aliyah Students - Rahmi, Shilla; Kholisin, Kholisin; Ainin, Moh. (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study develops an Articulate Storyline 360-based Interactive Arabic Learning Module for 10th-grade students at MA Al-Kautsar Trenggalek and describes its validity and feasibility. The research employs the R&D method, utilizing the ADDIE model, which encompasses the stages of analysis, design, development, implementation, and evaluation. Researchers collected quantitative and qualitative data through needs observation, expert validation questionnaires, and trial questionnaires administered to students and teachers. They used observation guidelines, material and media validation sheets, and feasibility questionnaires as data collection instruments. Thirty-eight tenth-grade students at Madrasah Aliyah Al-Kautsar participated as research subjects. Researchers analyzed quantitative data using a rating scale technique to obtain the percentage of validity and feasibility, and analyzed qualitative data descriptively. The results show that researchers successfully developed the module as an interactive learning medium containing audio, video, dialogues, four language skill exercises, and multimedia navigation. Content expert validation scored 78.5%, and media expert validation reached 97.3%. Field testing produced an 89% feasibility rating from teachers and an 81.8% rating from students, indicating that the module is practical for use in learning. These findings confirm that the Articulate Storyline 360-based interactive module is suitable for use as a supporting learning medium at MA Al-Kautsar and meets the need for more varied and interesting learning. Researchers recommend further research to test the effectiveness of the module in improving learning outcomes.